Planning For Strengthening Character Education In Sports And Physical Education Learning - CARSIWAN CARSIWAN; ACHMAD SANUSI; YOSAL IRIANTARA; DETI ROSTINI (Universitas Pendidikan Indonesia (UPI), 2022)
Introduction: Planning for strengthening character education in sports and physical education has not been appropriately designed. At the same time, the weight of character education in junior high school is 60% in learning. Purpose: The purpose of the study was to describe and analyze the planning for strengthening character education in learning physical education, sports, and health. The research uses a qualitative approach with a case study method. Methods: Research subjects PJOK teachers. Data collection techniques through observation, interviews, and documentation studies. Results: Data analysis with steps: reduction, data display, and concluding. Results Planning for strengthening integrated character education with physical education learning planning for sports and health has not been explicitly planned. The values of character education are only listed in core competence one and core competence two. They are not expressly described in the character values to be achieved in each lesson. The planning steps for strengthening character education are not detailed in the learning implementation plan program. Conclusions: Conclusion Planning for supporting character education in sports and health physical education learning has not been planned or designed correctly.